THE RELATIONSHIP BETWEEN KNOWLEDGE AND THE HABIT OF WASHING HANDS WITH SOAP IN STUDENTS AT PUBLIC ELEMENTARY SCHOOLS 013 SIMANGARONSANG - Taruli Rohana Sinaga; Kesaktian Manurung; R. Alyakin Dachi; Mido Ester Sitorus; Sri Dearmaita Purba; Putrina T. Olivia Purba (Jurnal Ilmiah Keperawatan, 2026)
Handwashing with soap represents the mechanical sanitization of dermal surfaces using cleansing agents and clean running water to eradicate pathogens, bacteria, and virus strains that potentially trigger various infectious clinical conditions. The primary goal behind promoting handwashing with soap is to suppress the transmission velocity of communicable agents. This empirical investigation was executed to chart the operational correlation between knowledge levels and the behavioral habit of handwashing with soap among learners at Public Elementary School 013 Simangaronsang, Doloksanggul District, Humbang Hasundutan Regency. Methodologically, This study adopts a quantitative approach using a cross-sectional model, drawing from a target population that simultaneously served as the total sample of 69 students from grades IV and V. Primary and secondary data collection was conducted utilizing a structured questionnaire instrument to evaluate the depth of student comprehension and determine the performance of the habit of handwashing with soap variable among the participants. Statistical hypotheses were verified using a bivariate Chi-Square test. The final research outcomes confirmed a highly significant relationship between health awareness and the practical habit of handwashing with soap, supported by an empirical p-value of 0.001. Based on these dynamics, there is an eye-opening need for tangible interventions to revitalize health infrastructure and deploy systematic educational schedules detailing accurate handwashing with soap steps through visual posters and audio-visual media, supplemented by furnishing robust sanitary assets and ensuring a stable supply of clean water within the school premises